2009
DOI: 10.1051/0004-6361/200911983
|View full text |Cite
|
Sign up to set email alerts
|

On the continuum intensity distribution of the solar photosphere

Abstract: Context. For many years, there seemed to be significant differences between the continuum intensity distributions derived from observations and simulations of the solar photosphere. Aims. In order to settle the discussion on these apparent discrepancies, we present a detailed comparison between simulations and seeing-free observations that takes into account the crucial influence of instrumental image degradation. Methods. We use a set of images of quiet Sun granulation taken in the blue, green and red continu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 50 publications
1
45
0
2
Order By: Relevance
“…This has been demonstrated repeatedly in the literature, for example, in studies looking at the limb darkening function (Pierce & Slaughter 1977;Neckel & Labs 1994), the intensity contrast of granulation (Sánchez Cuberes et al 2000;Danilovic et al 2008;Wedemeyer-Böhm & Rouppe van der Voort 2009;Afram et al 2011), and the brightness of small-scale magnetic concentrations (Title & Berger 1996;Schnerr & Spruit 2011) and sunspots (Albregtsen & Maltby 1981;Mathew et al 2007).…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…This has been demonstrated repeatedly in the literature, for example, in studies looking at the limb darkening function (Pierce & Slaughter 1977;Neckel & Labs 1994), the intensity contrast of granulation (Sánchez Cuberes et al 2000;Danilovic et al 2008;Wedemeyer-Böhm & Rouppe van der Voort 2009;Afram et al 2011), and the brightness of small-scale magnetic concentrations (Title & Berger 1996;Schnerr & Spruit 2011) and sunspots (Albregtsen & Maltby 1981;Mathew et al 2007).…”
Section: Introductionmentioning
confidence: 57%
“…A quantitative comparison of the rms intensity contrast of the quiet Sun presented here for HMI and other measurements reported in the literature would require taking into account instrumental differences such as the spatial resolution and bandpass, which is beyond the scope of this study. Due to HMI's limited spatial resolution, the rms contrast, even after image restoration with K 2 , remains below the values returned from spaceborne and balloon-borne (i.e., similarly seeing-free) observatories at finer spatial resolutions, namely Hinode (Danilovic et al 2008;Mathew et al 2009;Wedemeyer-Böhm & Rouppe van der Voort 2009) and SUNRISE (Hirzberger et al 2010). (Note though, that the divergence is also due in part to the different bandpass of the various instruments.…”
Section: Granulation Contrastmentioning
confidence: 97%
“…Magnetohydrodynamical simulations with a horizontal cell size of 20 km or larger are widely used in the literature (Afram et al 2010(Afram et al , 2011Hirzberger et al 2010;Orozco Suárez 2008;Röhrbein et al 2011;Wedemeyer-Böhm & Rouppe van der Voort 2009). We found a reduction of the effective BP diameter of 20% and a near doubling of the BP number density by doubling the horizontal grid resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Danilovic et al 2008;Wedemeyer-Böhm & Rouppe van der Voort 2009;Pereira et al 2009c;Hirzberger et al 2010;Afram et al 2011). We used a kernel with two components, i.e.…”
Section: Spatial Degradationunclassified
“…Asplund et al 2000;Wedemeyer-Böhm & Rouppe van der Voort 2009;Asplund et al 2009;Afram et al 2011), as well as in terms of the match between average synthetic and observed profiles (e.g. Asplund et al 2000).…”
Section: Introductionmentioning
confidence: 98%